Crystal Engineering Of Quercetin By Liquid Assisted Grinding Method - Athiyah, Umi (Universiti Teknologi Malaysia, 2018)
Quercetin has been proposed to exhibit numerous pharmacological benefits yet suffer low bioavailability due to the extremely low solubility. A research to study the impact of cocrystallization of quercetin with succinic acid on the solubility and dissolution profile has been performed. Cocrystallization in molar stoichiometry of 1:1 was carried out via liquid assisted grinding with methanol in ball milling apparatus. Cocrystal formation was identified by hot stage microscopy (HSM) at first, then cocrystal phase was characterized using differential thermal analysis (DTA), powder X-ray diffractometry (PXRD), scanning electron microscopy (SEM), and fourier-transform infrared (FT-IR) spectroscopy. Solubility and dissolution test were conducted as well. DSC thermogram exhibits new endothermic peak at 280.32C representing the melting point of cocrystal phase alongside with endothermic point of pure compounds. Powder X-ray diffractograms show new diffraction peaks on behalf of cocrystal formation at 2θ=8.92, 9.88, 13.04, 29.78, 35.35. FT-IR spectroscopy reveals band shifting in –OH group region. On SEM photographs, one can observe crystal habit of succinic acid being covered by crystal with different habit. This indicates that quercetin interacts with succinic acid only on the surfaces and causes imperfect formation of cocrystal phase. Cocrystallization quercetin improves solubility by 1.62 times higher and dissolution rate by 1.25 higher than pure quercetin (one-way ANOVA, p < 0.05).